RFID in the Retail sector: A Bibliographic review of the literature - Bruno Valdivia, Giordano Sebastian (2022)
All of the companies in the Retail sector, regardless of their size and age, have suffered different problems related to their stock and one solution is the use of radio frequency identification (RFID). Therefore, tracking and understanding the development of the literature on RFID is a key factor in the improvement of supply chain management (SCM). The general objective of this bibliographic review is to understand the behavior of the researches about the implementation of RFID in the Scopus database. In order to achieve the objective, the database will be filtered and subsequently analyzed using the VOSviewer software and bibliometrix software. In addition, the results shows the countries with the most publication as well as authors, journals and keywords.